Identification of areas of potential land-use conflict in the Luján River basin, Argentina. - Buzai, Gustavo D. (2017)
Geography, as spatial science, relies on the use of quantitative methods applied with Geographical Information Systems (GIS). In this context, cartographic modeling and multicriteria evaluation techniques allowed the definition of a methodological strategy for identifying areas of potential conflict between land-use at a regional scale (LUCIS). The research is carried out in the Luján River basin with the objective of defining these areas as a consequence of future spatial competition between urban land use, agricultural production and conservation areas. The results obtained are an excellent tool to use in the field of land-use planning.